Unequal and Unprotected: Exploring Gender Wage Gap Among Precarious Workers in Indonesia - Muhammad Nabiel; Toshihiro Kudo; Raden Muhamad Purnagunawan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This paper addresses the persistent issue of the gender pay gap among precarious workers in Indonesia, where women still receive significantly less than their male counterparts. The lack of empirical focus on this problem drives the research. Filling this void, the paper analyses how structures and institutions affect uneven wage formation and gendered labor insecurity. Adopting a quantitative approach, the paper employs the Oaxaca-Blinder decomposition and quantile regressions (using the 2023 SAKERNAS dataset) to decompose wage differentials across the income distribution. The results show that women earn 35.6 percent less than men on average, and that over 70 percent of this gap is not accounted for by observable characteristics, demonstrating the existence of enduring structural discrimination. The disparity is highest at the lower tail of the wage distribution, suggesting a sticky floor effect. These results highlight the need for policy interventions that enhance care protection, implement pay parity, regularize informal work, and promote gender-responsive digital inclusion.